Primary brewery wastewater as feedstock for the yeast Rhodosporidium toruloides and the microalga Tetradesmus obliquus mixed cultures with lipid production. (February 2022) - Dias, Carla; Reis, Alberto; Santos, José A.L.; Gouveia, Luisa; Lopes da Silva, Teresa
Graphical abstract: Highlights: R. toruloides and T. obliquus pure and mixed cultures were grown on PBWW. R. toruloides did not grow in pure cultures but grew in mixed cultures. T. obliquus pure cultures grew on PBWW attaining higher DCW than in mixed cultures. PBWW supplemented with sugarcane molasses and urea was used to grow mixed cultures. A maximum lipid content of 26.3 % (w/w DCW) when PBWW + urea+100 g/l SCM was used. Abstract: Rhodosporidium toruloides and Tetradesmus obliquus pure and mixed cultures were grown on primary brewery wastewater (PBWW), with and without supplementation of sugarcane molasses (SCM) and urea. R. toruloides developed in pure cultures was not able to grow on PBWW, with or without supplementation, but grew in mixed cultures with the microalga T. obliquus in all media. In contrast, all T. obliquus pure cultures developed on PBWW, with and without supplementation, were able to develop. Higher biomass productivity (149.3 mg L −1 h −1 ) was obtained for the mixed culture using PBWW supplemented with 10 g L −1 of SCM and 2 g L −1 of urea. Therefore, a strategy to stimulate lipid production by R. toruloides and T. obliquus grown in mixed cultures with higher SCM concentrations (20, 40 and 100 g L -1 of SCM) was developed. The maximum lipid content (26.3 % (w/w DCW)) was obtained for the mixed culture developed on PBWW, supplemented with 100 g L -1 of SCM plus 2 g L -1 of urea, at t = 121 h. This work demonstrated the feasibility of using PBWW supplemented with SCM and urea as culture medium to grow R. toruloides and T. obliquus and to produce microbial lipids.